2006
DOI: 10.1128/iai.02061-05
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium marinum Erp Is a Virulence Determinant Required for Cell Wall Integrity and Intracellular Survival

Abstract: The Mycobacterium tuberculosis exported repetitive protein (Erp) is a virulence determinant required for growth in cultured macrophages and in vivo. To better understand the role of Erp in Mycobacterium pathogenesis, we generated a mutation in the erp homologue of Mycobacterium marinum, a close genetic relative of M. tuberculosis. erp-deficient M. marinum was growth attenuated in cultured macrophage monolayers and during chronic granulomatous infection of leopard frogs, suggesting that Erp function is similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…First, the time-course of death induced by M. abscessus is more rapid than with M. marinum, with up to 50% of embryos dying 5-7 dpi and 100% within 2 wk post infection (19,24,38). Second, despite the apparent lack of the ESX-1 secretion system, M. abscessus induces granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the time-course of death induced by M. abscessus is more rapid than with M. marinum, with up to 50% of embryos dying 5-7 dpi and 100% within 2 wk post infection (19,24,38). Second, despite the apparent lack of the ESX-1 secretion system, M. abscessus induces granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Derp M. marinum displayed an intracellular growth defect in individual zebrafish larval macrophages, thus was compromised at an earlier step than DRD1 (Fig. 1) (Cosma et al 2006). Despite having no intracellular growth defect, DRD1 was as attenuated as Derp for overall growth in the animals.…”
Section: Inside the Granuloma Mycobacteria Use The Granuloma As A Vehmentioning
confidence: 99%
“…The latter genes are located in the well-known RD1 region, which is the distinctive mutation in the tuberculosis vaccine strain BCG. Injection of this mutant in zebrafish embryos resulted in aberrant granuloma formation in zebrafish embryos (Cosma et al, 2006;Gao et al, 2006;Volkman et al, 2004). This finding inspired us to do a forward genetic screen to identify M. marinum mutants impaired in granuloma formation in zebrafish embryos.…”
Section: Infectious Diseasementioning
confidence: 99%
“…To further establish the zebrafish tuberculosis model, it was shown that M. marinum mutants of important M. tuberculosis virulence factors, such as the cell surface protein Erp and the secreted ESAT-6 and CFP-10 proteins, are attenuated in the zebrafish model (Cosma et al, 2006;Gao et al, 2006;Volkman et al, 2004). The latter genes are located in the well-known RD1 region, which is the distinctive mutation in the tuberculosis vaccine strain BCG.…”
Section: Infectious Diseasementioning
confidence: 99%